Mechanistic insights into heat shock protein 27, a potential therapeutic target for cardiovascular diseases - Zou, Yifei; Shi, Henghe; Liu, Ning; Wang, He; Song, Xianjing; Liu, Bin (Frontiers in Cardiovascular Medicine, 2023)
Heat shock protein 27 (HSP27) is a small chaperone protein that is overexpressed in a variety of cellular stress states. It is involved in regulating proteostasis and protecting cells from multiple sources of stress injury by stabilizing protein conformation and promoting the refolding of misfolded proteins. Previous studies have confirmed that HSP27 is involved in the development of cardiovascular diseases and plays an important regulatory role in this process. Herein, we comprehensively and systematically summarize the involvement of HSP27 and its phosphorylated form in pathophysiological processes, including oxidative stress, inflammatory responses, and apoptosis, and further explore the potential mechanisms and possible roles of HSP27 in the diagnosis and treatment of cardiovascular diseases. Targeting HSP27 is a promising future strategy for the treatment of cardiovascular diseases.